Chronic effects of maternal tobacco-smoke exposure and/or ?-lipoic acid treatment on reproductive parameters in female rat offspring - Guzel, Elif Erdem; Kaya, Nalan; Tektemur, Ahmet; Ulker, Nazife; Yardimci, Ahmet; Akkoc, Ramazan Fazil; Ozan, Ibrahim Enver (Taylor & Francis Inc, 2020)
Prenatal tobacco-smoke exposure negatively affects the reproductive functions of female offspring and oxidative stress plays a major role at this point. Alpha-lipoic acid (ALA), well known as a biological antioxidant, has been used as a nutritional supplement and as a therapeutic agent in the treatment of certain complications during pregnancy. We aimed to investigate the effects of maternal tobacco-smoke exposure and/or ALA administration on puberty onset, sexual behavior, gonadotrophin levels, apoptosis-related genes, apoptotic cell numbers and oxidative stress markers in the adult female rat offspring. Sprague-Dawley rats were divided into four groups; control, tobacco smoke (TS), TS+ALA and ALA groups. Animals were exposed to TS and/or ALA for 8 weeks before pregnancy and throughout pregnancy. All treatments ended with birth and later newborn female rats were selected for each experimental group. The experiment ended at postnatal day 74-77. Maternal tobacco smoke advanced the onset of puberty in the female offspring of the TS group (p< 0.05). In all treatment groups; the mean number of anogenital investigations and lordosis quality scores showed a decline, serum luteinizing hormone levels significantly increased (p< 0.05) and several histopathological changes in ovaries were observed compared to the control group. In addition, an increase in apoptotic marker levels and apoptotic cell numbers was detected in the ovaries of all treatment groups. Decreased TAS and increased TOS levels were detected in all treatment groups compared to control. These findings suggested that maternal tobacco smoke and/or ALA administration may be leading to the impaired reproductive health of female offspring.
Keywords: Maternal tobacco smoke exposure; alpha-lipoic acid; puberty onset; sexual behavior; rat female offspring